The Effect of Midwife Assistance in Giving MPASI on Weight Growth of Infants Aged 6-24 Months - Hasnia; Rizqi Kamalah; Sumarah; Hasnawati Nukuhaly; Ni Made Dewianti (CV. Get Press Indonesia, 2026)
The assistance of midwives in complementary feeding (MPASI) is an important effort to prevent nutritional problems and support optimal baby growth. However, there are still babies with weight gain that does not match the standards due to improper complementary feeding practices and limited assistance from health workers. This study aims to analyze the effect of midwifery assistance in the provision of complementary foods on weight growth of infants aged 6-24 months. This research employed a quasi-experimental design utilizing a pretest-posttest control group approach, conducted within the working area of Ambacang Health Center, Padang. A total of 40 mothers with infants aged 6-24 months were recruited through purposive sampling and subsequently allocated into intervention and control groups. Over a three-month period, the intervention group received midwife-led assistance related to complementary feeding practices, while the control group continued to receive standard routine care. Data were analyzed using a paired t-test with a significance threshold set at 0.05. The findings revealed that infants in the intervention group experienced an average weight gain of 0.83 kg (range: 0.6–1.2 kg), which was higher than the 0.47 kg (range: 0.3–0.7 kg) observed in the control group. The paired t-test further demonstrated a statistically significant increase in body weight within the intervention group following the mentoring period (p=0.001). It was therefore concluded that midwife assistance in complementary feeding provision has a positive effect on weight gain among infants aged 6-24 months. Continuous mentoring is an effective strategy in supporting infant growth and preventing nutritional problems.